Detection of the circulating tumor cells in cancer patients. (December 2010) - Armakolas, Athanasios; Panteleakou, Zacharoula; Nezos, Adrianos; Tsouma, Aikaterini; Skondra, Maria; Lembessis, Peter; Pissimissis, Nikolaos; Koutsilieris, Michael
As the presence of tumor cells circulating in the blood is associated with systemic disease and shortened survival, the establishment of a method to detect circulating tumor cells (CTCs) is of critical importance for a more concise staging and follow-up of cancer patients. Recently, the most robust strategies for the determination of CTCs are the PCR-based methods and the CellSearch ® system that exploits the immunofluorescent characterization and isolation of cancer cells. Herein, we analyzed the experimental strategies used for determining CTCs with respect to accuracy, sensitivity and reproducibility in cancers of the breast, colon, prostate and melanoma.